Como o gradiente altitudinal de luz no sub-bosque afeta as características estruturais e fisiológicas de hemiepífitas: o caso de Vanilla bahiana Hoehne (Orchidaceae) - Buss, Aldineia (2020)
The epiphytic environment of understory imposes abiotic conditions peculiar to plants, which grow subject to fluctuations in water, light and nutrients, demanding plasticity to acclimatize. In the Cerrado, in addition to the light typical gradient of forest formations, epiphytic plants must deal with marked water seasonality. In this study, the effect of the light gradient formed by the understory of a gallery forest, and the water seasonality, on the leaf structure and physiology Vanilla bahiana Hoehne, a secondary hemiepiphyte, was evaluated. Different light conditions were considered in three strata along the phorophyte branch (up to 0.5 m; 2 to 2.5 m; 3.5 to 4 m), in dry and rainy seasons. Vanilla bahiana showed itself as a strong CAM (values of δ13C between -15.62 and -17.62 5 ‰). Despite the higher chlorophyll content, the leaves close to the ground (shaded ones) showed lower size, biomass and specific leaf mass. The leaves in the highest strata of the understory (under more radiation) showed a greater effect of water seasonality, with higher accumulation of organic acids at night and higher rates of conductance and electron transport in the rainy season. The drought reduced the period of stomatal opening, increased transpiration and modified the CAM phases, maintaining II and IV phases occurring entirely during the dark in all strata. In the more shaded leaves, strategies for light capture and energy processing were observed, while the leaves receiving more light showed greater carbon fixation.